Physical Education Activities in Sports Schools (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, the description, structure, and stages of the work of children's sports schools are described in detail. Sports schools specializing in the preparation of Olympic reserves for children and teenagers are separate or equipped with a sports base and highly qualified coaches-teachers. organization under schools is justified